2013
DOI: 10.1167/iovs.13-13140
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Human Papillomavirus in Ocular Surface Diseases

Abstract: The low prevalence of HPV-16 in ocular surface disease suggests infection is not a cause but a cofactor in disease development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 64 publications
2
28
0
2
Order By: Relevance
“…The vast majority of HPV types cause benign warts of the skin or genital region (Table 1) (8)(9)(10)(11)(12)(13). Some HPV types have the potential to cause lesions that progress to cancer.…”
mentioning
confidence: 99%
“…The vast majority of HPV types cause benign warts of the skin or genital region (Table 1) (8)(9)(10)(11)(12)(13). Some HPV types have the potential to cause lesions that progress to cancer.…”
mentioning
confidence: 99%
“…DNA quality and yield are generally better from fresh specimens than preserved specimens, but the unavailability of fresh specimens may be a common roadblock to these studies, as tissue is typically submitted for histopathological examination (Woods et al, 2013). Therefore, FFPE samples represent an important source for retrospective studies (Newkirk et al 2014); however, the use of an adequate fixation process to conserve tissue morphology may negatively affect nucleic acid preservation and may consequently also affect molecular diagnostic procedures (Barcelos et al, 2008).…”
mentioning
confidence: 99%
“…Therefore, a screening PCR assay using FFPE samples should be performed in parallel with reactions that amplify a housekeeping gene of similar size to ensure the DNA is not compromised and is amenable to PCR (Woods et al, 2013). In this study, a PCR assay for equine β-actin (reference gene) was used to confirm that the DNA purification methods were efficient and that the samples contained sufficient amplifiable DNA.…”
mentioning
confidence: 99%
“…Moreover, no putative pRB binding sites (LXCXE) have been identified in equine papilloma viruss (EcPV-2) and 3 E7 amino acid sequences, so E7 is probably not able to modulate pRB and consequently the p16 protein. In human pathology the prevalence of HPV in ocular surface disease varies dramatically, according to variations in the assays used to detect the virus, as well as geography and genetic susceptibility (Woods et al 2013), and the utility of p16INK4a immunoexpression for predicting HPV in ocular surface squamous neoplasia was evaluated but, unlike cervical cancers, it seems that there is no correlation. In fact, the overexpression of p16INK4a in OSSN was significantly associated with HPV (Chauhan et al 2012), while Auw-Haedrich et al (2008) have reported HPV and p16INK4a positivity in conjunctival intraepithelial neoplasias (CIN) but they did not observe any association between p16INK4a and HPV.…”
Section: Discussionmentioning
confidence: 99%